Chlamydomonas reinhardtii PsbS Protein Is Functional and Accumulates Rapidly and Transiently under High Light. Issue 4 (21st June 2016) - Tibiletti, Tania; Auroy, Pascaline; Peltier, Gilles; Caffarri, Stefano
Abstract : Photoprotective proteins PsbS and LhcSR3 accumulate rapidly in the photosynthetic membrane of Chlamydomonas during highlight stress with PsbS activating nonphotochemical quenching. Abstract: Photosynthetic organisms must respond to excess light in order to avoid photo-oxidative stress. In plants and green algae the fastest response to high light is non-photochemical quenching (NPQ), a process that allows the safe dissipation of the excess energy as heat. This phenomenon is triggered by the low luminal pH generated by photosynthetic electron transport. In vascular plants the main sensor of the low pH is the PsbS protein, while in the green alga Chlamydomonas reinhardtii LhcSR proteins appear to be exclusively responsible for this role. Interestingly, Chlamydomonas also possesses two PsbS genes, but so far the PsbS protein has not been detected and its biological function is unknown. Here, we reinvestigated the kinetics of gene expression and PsbS and LhcSR3 accumulation in Chlamydomonas during high light stress. We found that, unlike LhcSR3, PsbS accumulates very rapidly but only transiently. In order to determine the role of PsbS in NPQ and photoprotection in Chlamydomonas, we generated transplastomic strains expressing the algal or the Arabidopsis psbS gene optimized for plastid expression. Both PsbS proteins showed the ability to increase NPQ in Chlamydomonas wild-type and npq4 (lacking LhcSR3) backgrounds, but no clear photoprotection activity was observed. Quantification of PsbS and LhcSR3 in vivo indicates that PsbS is much less abundant than LhcSR3 during high light stress. Moreover, LhcSR3, unlike PsbS, also accumulates during other stress conditions. The possible role of PsbS in photoprotection is discussed.